Laura Schmidt: Weihnachtliches Theater. Zur Entstehung und Geschichte einer bürgerlichen Fest- und Theaterkultur, Bielefeld 2017 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Inklusion und Intersektionalität im Kontext frühkindlicher Medienbildungsforschung. Sprachkulturelle Homogenität und Diversität sowie ihre Auswirkungen auf pädagogische Kommunikation in der Frühen Bildung - Günesli, Habib (QfI - Qualifizierung für Inklusion Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
Dieser Beitrag basiert auf den Ergebnissen eines im Jahr 2019 abgeschlossenen Promotionsvorhabens im Rahmen des interventiv angelegten, in Dortmund angesiedelten, Forschungsprojekts KidSmart – Medienkompetent zum Schulübergang zu den Mediensozialisationsbedingungen von deutschen, deutsch-türkischen und deutsch-anderen vier und fünf Jahre alten Mädchen und Jungen in den sozialen Feldern Familie und Kita. Im vorliegenden Beitrag wird auf die Befragung der ErzieherInnen fokussiert, die mittels halbstandardisierter Fragebögen durchgeführt wurde. Untersucht wurde, wie sich der sprachlich-kulturelle Hintergrund der Kinder für das Kommunikationsverhalten der ErzieherInnen mit den Kindern in pädagogischer Anschlusskommunikation und in Gesprächen mit den Eltern der Kinder auswirkt. Hier wurde auch eine intersektionale Perspektive eingenommen und parallel zur Herkunftskultur auch das biologische Geschlecht der Kinder in die Auswertung einbezogen. Es stellte sich heraus, dass die Kommunikation sowohl mit den Kindern als auch mit den Eltern in Abhängigkeit der Herkunftskultur der Kinder und auch ihres Geschlechtes erfolgt. Pädagogisch ist zu fragen, inwiefern es den pädagogischen Fachkräften gelingt, benachteiligende Ausgangslagen auch tatsächlich auszugleichen und Partizipation im Sinne von Inklusion zu ermöglichen. Ausgehend von diesen Ergebnissen wird in diesem Beitrag die Bedeutung und Relevanz der Überschneidungen und Interdependenzen von Ungleichheitsdimensionen für eine inklusionsorientierte Qualifikation pädagogischer Fachkräfte in institutionell-frühkindlichen Medienbildungskontexten diskutiert. Konkret richtet sich der Blick auf die sprachlich-kulturelle Ein- und Vielfalt in den frühkindlichen Einrichtungen sowie die Wahrnehmungen und Einschätzungen der pädagogischen Fachkräfte, die sie in Hinblick auf die Kooperationswilligkeit der Eltern, die Anschlusskommunikation mit den Kindern und schließlich die medialen Fähig- und Fertigkeiten der Kinder äußern.

Regularizing neural networks with gradient monitoring - Chadha, Gavneet Singh; Meydani, Elnaz; Schwung, Andreas (Recent Advances in Big Data and Deep Learning: Proceedings of the INNS Big Data and Deep Learning Conference INNSBDDL2019, held at Sestri Levante, Genova, Italy 16-18 April 2019)

Probing nonclassicality with matrices of phase-space distributions - Bohmann, Martin; Agudelo, Elizabeth; Sperling, Jan (Quantum)
We devise a method to certify nonclassical features via correlations of phase-space distributions by unifying the notions of quasiprobabilities and matrices of correlation functions. Our approach complements and extends recent results that were based on Chebyshev's integral inequality \cite{BA19}. The method developed here correlates arbitrary phase-space functions at arbitrary points in phase space, including multimode scenarios and higher-order correlations. Furthermore, our approach provides necessary and sufficient nonclassicality criteria, applies to phase-space functions beyond s-parametrized ones, and is accessible in experiments. To demonstrate the power of our technique, the quantum characteristics of discrete- and continuous-variable, single- and multimode, as well as pure and mixed states are certified only employing second-order correlations and Husimi functions, which always resemble a classical probability distribution. Moreover, nonlinear generalizations of our approach are studied. Therefore, a versatile and broadly applicable framework is devised to uncover quantum properties in terms of matrices of phase-space distributions.

Classical evolution in quantum systems - Sperling, Jan; Walmsley, I A (Physica Scripta)

Transfer function replacement of phenomenological single-mode equations in semiconductor microcavity modeling - Carcamo, M.; Schumacher, Stefan; Binder, R. (Applied Optics)
Semiconductor microcavities are frequently studied in the context of semiconductor lasers and in application-oriented fundamental research on topics such as linear and nonlinear polariton systems, polariton lasers, polariton pattern formation, and polaritonic Bose–Einstein condensates. A commonly used approach to describe theoretical properties includes a phenomenological single-mode equation that complements the equation for the nonlinear optical response (interband polarization) of the semiconductor. Here, we show how to replace the single-mode equation by a fully predictive transfer function method that, in contrast to the single-mode equation, accounts for propagation, retardation, and pulse-filtering effects of the incident light field traversing the distributed Bragg reflector (DBR) mirrors, without substantially increasing the numerical complexity of the solution. As examples, we use cavities containing GaAs quantum wells and transition-metal dichalcogenides (TMDs).
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

Chiral condensates in a polariton hexagonal ring. - Ma, Xuekai; Kartashov, YV; Kavokin, A; Schumacher, Stefan (Optics Letters)

Carbon vacancy-related centers in 3C-silicon carbide: Negative-U properties and structural transformation - von Bardeleben, H. J.; Rauls, E.; Gerstmann, Uwe (Physical Review B)

Electron paramagnetic resonance study of ferroelectric phase transition and dynamic effects in a Mn2+ doped [NH4][Zn(HCOO)3] hybrid formate framework - Navickas, Marius; Giriūnas, Laisvydas; Kalendra, Vidmantas; Biktagirov, Timur; Gerstmann, Uwe; Schmidt, Wolf Gero; Mączka, Mirosław; Pöppl, Andreas; Banys, Jūras; Šimėnas, Mantas (Physical Chemistry Chemical Physics)
EPR spectroscopy reveals the universality class and dynamic effects of the [NH4][Zn(HCOO)3] hybrid formate framework.

Spin-orbit driven electrical manipulation of the zero-field splitting in high-spin centers in solids - Biktagirov, Timur; Gerstmann, Uwe (Physical Review Research)
Keywords: General Engineering